Performance Optimization of Airport Control Area Pass System Based on Huawei Kunpeng - Zhang, Haonan; Cao, Tie; Shao, Liming; Tu, Hao (International Journal of Computer Science and Information Technology, 2025)
At present, there are many problems in the supervision and industry services of personnel in airport control areas, mainly focused on data governance capabilities. Based on this pain point, develop a national airport control area pass personnel management system to achieve online application, approval, issuance, replacement, and reissuance of airport control area passes, achieve unified supervision and standardized processes, and comprehensively enhance safety supervision and management capabilities and data sharing capabilities. Compared to traditional X86 architecture, processors based on ARM architecture provide higher memory bandwidth. The pass system was successfully ported to the Huawei Kunpeng processor based on ARM architecture for testing and performance comparison with x86 architecture. The results showed that Huawei Kunpeng had significant performance optimization in both single core and multi-core computing efficiency compared to x86 architecture. The rapid development of domestic chip technology is fully empowering the digitalization of the civil aviation industry.